PERLINDUNGAN HAK PEKERJA PKWT TERHADAP PEMBERIAN KOMPENSASI DI PERUSAHAAN - Rahmatullah, Rahmatullah; Effendi, Ria Regger; Santoso, Imam Budi (Legal Standing : Jurnal Ilmu Hukum, 2024)
This study aims to find out the extent of the impact of the enactment of Law number 11 of 2020 concerning job creation which has been legalized as a law at the level of practice in the Company. The enactment of this law brings very significant changes to companies with the obligation to provide compensation at the end of the PKWT. This is a new problem for the business world which is classified as middle to lower so as to meet it a wide variety of policy variations in relation to providing other benefits to balance costs for the sustainability of the next business. This article examines how the protection of PKWT, which has some other benefit rights, is reduced due to balancing company expenses. This research uses normative research methods with an analytical descriptive approach where this article describes the phenomena that occur in companies that are classified as middle to lower class so as to ensure the problems that occur and are studied normatively. So that with this article, it is hoped that there will be policy changes made by the government to the conditions after the enactment of Law number 11 of 2020 concerning job creation, especially in the arrangement for providing compensation money at the end of PKWT workers so that the business continuity and rights of PKWT employees can all be fulfilled properly.